Meta-Analysis Summary of Broiler Chicken Trials with Dietary Actigen® (2009-2011) - Hooge , Danny M.; Connolly, Aidan (International Journal of Poultry Science, 2011)
Statistical meta-analyses of results from broiler trials in 2009-2011 using dietary Actigen® were conducted. Actigen® (Alltech, Inc., Nicholasville, Kentucky, USA) is a second-generation, yeast cell wall product considered to be a "growth permitter" through its roles in immune modulation and improved intestinal health. Parameters evaluated were dietary inclusion rates for Actigen®, age of birds, Body Weight (BW), feed conversion ratio or feed/gain ratio and mortality %. Nine reports were collected allowing 15 comparisons of negative control (nCON) diets and Actigen® supplemented diets fed during the entire trials. Similarly, 9 reports were collected allowing 11 comparisons of positive control (antibiotic supplemented) diets and Actigen® supplemented diets. When added to basal diets, Actigen® at average inclusion rates by phases of 520/400/347 g/tonne (n = 15) and broiler age of 41.87 days (n = 15) significantly and beneficially changed body weight by +0.129 kg (+5.41%), feed conversion ratio or feed/gain ratio by -0.046 (-2.54%) and mortality % by -0.76 (-10.5% relative to nCON). Compared with positive control (antibiotic) results, dietary Actigen® at average inclusion rates by phases of 535/331/238 g/tonne (n = 11) and broiler age of 43.64 days (n = 11) non significantly changed body weight by +0.016 kg (+0.62%), feed conversion ratio or feed/gain ratio by -0.003 (-0.17%) and mortality % by +0.57 (+7.97% relative to positive control). Broiler results for antibiotic or Actigen® supplemented diets were statistically equivalent. Comparisons between this present meta-analysis and those done previously on another yeast cell wall compound (Bio-Mos®) suggest that the second generation product Actigen® may be more effective in terms of growth promotion.